Optimal sizing and renewable integration for green ammonia plants in South Africa - Woods, Joshua Anderton (Stellenbosch : Stellenbosch University, 2025)
Woods, J. A. 2025. Optimal Sizing and Renewable Integration for Green Ammonia Plants in South Africa. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5f6b5352-062c-48b7-907f-d4abc1f0d79f